AKTIVITAS ANTIMIKROBA ISOLAT BAKTERI ASAM LAKTAT DARI KULIT ARI KACANG KEDELAI TERHADAP ESCHERICHIA COLI DAN STAPHYLOCOCCUS AUREUS - Megawati Saputri; Evy Rossi; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the antimicrobial activity of lactic acid bacteria isolate from soybean epiderm against pathogens Escherichia coli 0157 and Staphylococcus aureus ATCC-25329. The experiment was conducted experimentally using Randomized Complete Design (RAL) with three treatments and five replications to obtain 15 experimental units. The treatment used lactic acid bacteria isolates from soybean epiderm namely K.12.3, K.13.1 and K.22.1 tested in petri dish that already contained pathogenic bacteria Staphylococcus aureus ATCC-25923 and Escherichia coli 0157. Antimicrobial activity was tested using well agar diffusion method and the data obtained were analyzed using ANOVA and continued with DNMRT advanced test at 5% level. The results showed that the lactic acid bacteria of the soybean epiderm had a greater inhibition against Escherichia coli 0157 compared with Staphylococcus aureus ATCC-25923. Isolate K.13.1 was not significantly different in inhibiting Escherichia coli 0157 which resulted in inhibition zone of 8.313 mm and Staphylococcus aureus ATCC-25923 with inhibition zone of 6.960 mm. Mean while, the cell-free supernatant K.22.1 isolate significantly different in inhibiting Escherichia coli 0157 with inhibition zone of 6.860 mm and Staphylococcus aureus ATCC-25923 resulted in inhibition zone of 5.760 mm. Keyword : Lactic acid bacteria, inhibition zone, pathogen bacteria